The impact of guanxi on logistics service value - Poti Chao (2018)
Under the context of relationship, the concept of guanxi is an ambiguous term that embeds Chinese philosophy of social structure and interactions. The purpose of this study is to examine the relationship between logistics service value, relationship quality, guanxi and the financial performance of Thai shippers. To do so, this study uses a structural equation model (SEM), as it is the most appropriate multivariate analytical technique to estimate multiple and interrelated dependent relationships. The method embraces unobserved concepts that are termed constructs, latent variables and factors, thus allowing the researcher to handle a large number of endogenous and exogenous variables (Hair et al., 2010). The study results show that guanxi had a significant positive effect on logistics service value and financial performance. Logistics service value, however, did not have a significant effect on financial performance, nor did guanxi on relationship quality. The results provide a better understanding of the role relationships play in the context of logistics service value and how it can affect financial performance. They also can be used as a guideline in making strategic business decisions with Asian businesses.